Richard II [videorecording (DVD)] - Tennant, David, 1971-; Hamilton, Emma, 1984-; Pennington, Michael, 1943-; Lindsay, Nigel, 1969-; Davies, Oliver Ford; Cruickshank, Marty; Rix, Olly; Lapotaire, Jane; Griffiths, Marcus; Hooper, Jim; Osborn, Keith; Richards, Josh (Actor), active 1987-; et al. (Shakespeare's globe (Opus Arte), 2014)
"Richard is King. A monarch ordained by God to lead his people. But he is also a man of very human weakness. A man whose vanity threatens to divide the great houses of England and drag his people into a dynastic civil war that will last 100 years"--Container.